A novel, easy method for estimating pheromone trap attraction range: application to the pine sawyer beetle Monochamus galloprovincialis. (4th July 2018) - Jactel, Herve; Bonifacio, Luis; van Halder, Inge; Vétillard, Fabrice; Robinet, Christelle; David, Guillaume
Abstract: Pheromone traps are widely used for monitoring or managing insect pest populations. However, it is important to know their range of attraction to optimize the setting of pheromone trap networks. We propose an easy method based on the use of pairs of adjacent traps located at decreasing distance from each other. The range of attraction is deduced from the observation of reduced trap capture when the attraction range of two adjacent traps starts overlapping. The relationship between the relative trap capture and the distance between paired traps is fitted with a logistic curve. To empirically test these predictions, we conducted trapping experiments with the beetle Monochamus galloprovincialis, the insect vector of the pine wood nematode. Fifteen pairs of traps separated by 25 to 300 m, in France, and 18 pairs of traps distant from 25 to 400 m, in Portugal, were installed in maritime pine plantation landscapes. In both countries, the relative percentage of capture per trap per week was best fitted by a logistic model with two parameters. The estimated attraction ranges were 92 m (confidence interval = 62–211 m) in France and 123 m (confidence interval = 64–491 m) in Portugal. The interference between paired traps thus provides a simple and robust method for estimating the attraction range of pheromone traps.